2019
DOI: 10.1186/s13018-019-1494-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis and clinical outcomes of intraoperative periprosthetic fractures: a retrospective study of 481 bipolar hemiarthroplasties

Abstract: Background: Intraoperative periprosthetic fractures (IPF) are a well-described complication following hip hemiarthroplasty. Our aims were to identify risk factors that characterize IPF and to investigate postoperative mobility. Methods: We retrospectively reviewed 481 bipolar hemiarthroplasties for displaced femoral neck fractures; of which, 421 (87.5%) were performed without cement, from January 2013 to March 2018. Data on the patients' demographics, comorbidities, femoral canal geometry (Dorr canal type, Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
(68 reference statements)
2
6
0
Order By: Relevance
“…Our retrospective study found 34 (6.6%) isolated GTFs which is in line with other studies that found GTFs in 4.1–6.3% following HA in patients with a femoral neck fracture [ 12 14 ]. The only patient-related risk factor for intraoperative GTF identified in our study was a decreased prothrombin time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our retrospective study found 34 (6.6%) isolated GTFs which is in line with other studies that found GTFs in 4.1–6.3% following HA in patients with a femoral neck fracture [ 12 14 ]. The only patient-related risk factor for intraoperative GTF identified in our study was a decreased prothrombin time.…”
Section: Discussionsupporting
confidence: 92%
“…However, patients in this study presented with mean 25OH-vitamin D3 levels of 20 ng/ml, whereas hip fracture patients in our region exhibit significantly lower levels with a median of 8.4 ng/ml as shown previously [ 17 ]. Hong et al found no difference of T-Scores between groups, but identified Dorr C type femoral canals [ 18 ] as a risk factor for intraoperative fractures as did Bellova et al [ 14 ]. Since we focused on isolated GTF, the Dorr types of the femoral canals were not determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized treatment responses within the hip may influence the likelihood of fractures initiating or propagating within the affected subregion, and might also have implications for the fixation of orthopedic implants including hip prostheses. ( 15–17 )…”
Section: Introductionmentioning
confidence: 99%
“…Localized treatment responses within the hip may influence the likelihood of fractures initiating or propagating within the affected subregion, and might also have implications for the fixation of orthopedic implants including hip prostheses. (15)(16)(17) Cortical and trabecular bone parameters are typically obtained via imaging modalities that rely on 3D quantitative computed tomography (QCT)-based technologies. Such modalities were not included in ACTIVE or ACTIVExtend, but standard two-dimensional (2D) hip dual energy X-ray absorptiometry (DXA) scans can now be processed using 3D-DXA software to model cortical and trabecular measurements, with results that correlate well with QCT results.…”
Section: Introductionmentioning
confidence: 99%